TiO2 nanotube layers decorated by titania nanoparticles as anodes for Li-ion microbatteries - Sopha, Hanna; Ghigo, Clement; Ng, Siow Woon; Alijani, Mahnaz; Hromadko, Ludek; Michalicka, Jan; Djenizian, Thierry; Macak, Jan M. (Materials Chemistry and Physics, 2022)
In this work, the utilization of TiO2 nanotube (TNT) layers decorated with TiO2 nanoparticles (NPs) as anodes in Li-ion microbatteries is reported for the first time. Such TiO2 NPs decorated TNT layers possess an increased amount of active material and a higher surface area compared with their non-decorated (blank) counterparts. TNT layers decorated with several different amounts of TiO2 NPs were tested by galvanostatic cycling tests. The capacities of the TiO2 NPs decorated TNT layer anodes increase with the amount of NPs decoration due to the enhancement of the capacitive effect. Indeed, an areal capacity of ∼126 μAh cm−2 (vs 88 μAh cm−2 for the non-decorated TNT layer) at the 200th cycle has been obtained after optimizing the NPs loading. On the other hand, a too high NPs loading of the TNT layers leads to a reduced areal capacity due to clogging of the nanotube exteriors and a significant decrease in inner diameter of the nanotubes.
CRIS-Team Scopus Importer:2022-11-02
Keywords: Decoration; Li-ion microbatteries; TiO; TiO